Comparative evaluation of interleukin-10, transforming growth factor-β, and interleukin-17 in gastrointestinal tuberculosis and crohn's disease - Anjali Gupta; Kusum Sharma; Vishal Sharma; Jagdeep Singh; Ritambhra Nada; Biman Saikia; Ranjana W Minz; Shashi Anand; Mahendra Kumar (International Journal of Mycobacteriology, 2022)
Background: Gastrointestinal tuberculosis (GITB) and Crohn's disease (CD) are close mimickers and difficult to discriminate. Recent work has focused on the immunological differences between GITB and CD based on cytokines related to T-regulatory cells and Th17 cells. In the present cross-sectional study, suspected cases of GITB or CD underwent extensive clinical, radiological, endoscopic, histological, and microbiological assessment. The diagnosis was based on standard criteria and response to antitubercular therapy endoscopically. Methods: Interleukin (IL)-10, transforming growth factor-β (TGF-β), and IL-17 were measured and compared between GITB and CD along with other parameters. Fisher's exact test and Mann–Whitney U test were used as per the data type. Results: Of the 27 patients, 11 had CD, 9 had GITB, and 7 had other conditions. Chronic diarrhea, involvement of left and long segments of the colon, and aphthous ulcers were significantly more frequent in CD; however, transverse ulcers were in GITB. IL-10 was reduced in both GITB (median-interquartile range [IQR] 9.54 [3.65–24.04]) and CD (median-IQR 13.28 [6.91–22.50]) compared to control (median-IQR 26.72 [10.34–35.43]). TGF-β showed little variation, but IL-17 was below the detection limit in most cases. None of these cytokines were significantly different between CD and GITB. The sensitivity and specificity of multiplex Mycobacterium tuberculosis-polymerase chain reaction were 44.44% and 100%, respectively. Conclusion: Serum cytokine profiling (IL-10, IL-17, and TGF-β) could not significantly differentiate GITB and CD. Moreover, extensive molecular, transcriptomic, chemokines, and cytokine analyses may shed light on these aspects.